GAOK'S ORAL TRADITION DOCUMENT MANAGEMENT AS A MANIFESTATION OF CULTURAL PRESERVATION IN THE LIBRARY - Septa, Septa; Heriyanto, Heriyanto (Record and Library Journal, 2020)
Background of the study: This research identifies ways of the document management of local oral traditions in Majalengka.Purpose: It aims to uncover how the library has managed the local oral document which intended to preserve the Gaok local content.Method: A qualitative method was implemented by using semi-structured interviews as a data collection technique. The collected data were then analyzed by using Thematic Analysis, which generates three themes related to the research questions. The themes are Motivation, Document Management, and Dissemination Planning. Findings: Motivation describes the background of the initiative by managing the Gaok Oral Documents. While the second theme, Document Management, portrays the effort taken by the library in managing the documents, that include retrieving information about Gaok, writing its resume, and disseminate the information. Finally, the third theme,  Dissemination Plan, describing the library strategic plans on disseminating and implementing their strategy of the Gaok Documents locally and nationally. The library believes that by managing the Gaok Oral Documents effectively, this local tradition will keep alive and known and hopefully preserved by the future generations.Conclusion: This study reflects how a library plays an important role in managing and preserving local culture.